Quantitative Analysis of Cephradine using the Modern High-performance Liquid Chromatographic Method (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Cephradine is the most important type of antibiotics used vary widely. Analysis of these antibiotics is the challenge because of their sensitivity and instability to different conditions. Objective: The present article is extended to find out HPLC method. Materials and Methods: The Standard Solution 100 Î¼g/ml Cephradine was prepared by dissolving accurately weight 100 mg of Cephradine in 1000 ml methanol and the range 2.5-12.5 Î¼g/ml was prepared by serial dilution of the sample with methanol. HPLC-UV system with Ion Pac column Zorbax 300-SCX Agilent Column; 5Î¼m, 4.6Ã—250 mm used for analysis for Cephradine in formulations capsules. The chromatographic conditions used for the analysis as well as analytical parameters study carried out with experimental conditions. HPLC method is the most common method for the analysis of Cephradine in formulation and in biological fluids, the several analytical procedures have been described for analysis of Cephradine in different pharmaceutical the formulations. Result and Discussion: During the study analytical parameters studied such as range, linearity, precision, accuracy, LLOD, LLOQ. Cephradine as formulation capsules was almost stable at room temperature up to 2-3 days in the aqueous medium at pH between 4 and 5. The focus of the study of analysis of Cephradine in formulation capsules is used for the determination of various Cephradine for supported by budding researchers. Conclusion: This study suggested a simple, easy and highly sensitive method using standardized samples obtained from the best international companies. Comparisons were made with different commercial samples of cephradine antibiotics. The actual ratios of cephradine were determined in commercial pharmaceuticals.